2021
DOI: 10.5217/ir.2019.09167
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of vedolizumab in Asian and non-Asian patients with ulcerative colitis and Crohn’s disease

Abstract: mediates lymphocyte trafficking to gastrointestinal mucosa and gut-associated lymphoid tissue through mucosal addressin cell adhesion molecule-1 (MAdCAM 1). 1 The novel mechanism of action of vedolizumab allows it to bind exclusively to the α 4 β 7 integrin, antagonizing its adherence to MAdCAM-1 and thereby impairing the migration of leukocytes into gastrointestinal mucosa. 1 The gut-selective, anti-inflammatory activity of vedolizumab enables targeted therapy without generalized immunosuppression. Vedolizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
2
22
2
Order By: Relevance
“…Although vedolizumab clinical efficacy was not explored in this post hoc analysis, real‐world data support the conclusion that ADAs do not appear to play a major role in vedolizumab efficacy, 24 even in patients who discontinue and later restart vedolizumab treatment 25,26 . This is further supported by previously published results 27 and that low‐titer ADA positive status (10‐50 titer values) had minimal effect on the pharmacokinetics of vedolizumab, 18 whereas higher‐titer ADAs (≥250 titer values) affect vedolizumab clearance 28 . Additionally, a recent report suggested that immunogenicity was not a primary driver of vedolizumab treatment failure 24 …”
Section: Discussionsupporting
confidence: 81%
“…Although vedolizumab clinical efficacy was not explored in this post hoc analysis, real‐world data support the conclusion that ADAs do not appear to play a major role in vedolizumab efficacy, 24 even in patients who discontinue and later restart vedolizumab treatment 25,26 . This is further supported by previously published results 27 and that low‐titer ADA positive status (10‐50 titer values) had minimal effect on the pharmacokinetics of vedolizumab, 18 whereas higher‐titer ADAs (≥250 titer values) affect vedolizumab clearance 28 . Additionally, a recent report suggested that immunogenicity was not a primary driver of vedolizumab treatment failure 24 …”
Section: Discussionsupporting
confidence: 81%
“…How long these medications last in the system and effect of low dose detectable levels on post-surgical outcomes is not well understood, but it has been suggested that even low dose can have negative effects on outcomes. 16,17 In our study, however, rates of complications with vedolizumab were still low in this potentially higher risk group of patients.…”
Section: Discussioncontrasting
confidence: 56%
“…The third step involves TDM during the maintenance phase when the measurement of mABs and ADAs may be appropriate for all anti-TNFα agents ( Papamichael et al, 2019a ), while the reactive TDM can be the standard of care for all IBD patients who experienced a loss of response. As presented in previous paragraphs, the titration of ADAs (rather than the notification of their presence or absence) could further improve the segmentation of patients according to their likelihood of response ( Brandse et al, 2017 ; Okamoto et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that two independent population pharmacokinetic studies found that the titer of ADAs correlated with the estimated clearance values of infliximab ( Brandse et al, 2017 ) and vedolizumab ( Okamoto et al, 2020 ) better than a simple dichotomic presence/absence result. These findings are likely suggesting that a more accurate segmentation of patients according to the ADA titer could further improve the individualization of therapeutic regimens.…”
Section: Monoclonal Antibodies Used In Inflammatory Bowel Diseasesmentioning
confidence: 99%